Gramsci's concept of the "subaltern" and the problematic of the peasantry - San Juan, Epifanio Jr. (2004)
Gramsci's concept of tthe subaltern arose from his application of materialist dialectics to the uneven development of the Italian social formation. It functioned as a key element in formulating the central idea of the hegemony of the working class based on an expansive alliance of various classes. Focusing on the ideological consent of all the oppressed, Gramsci departed from the narrow economistic and corporatist notion of class tied with sectarian workerism in Europe. Gramsci's marxist theory of the subaltern, however, should be distinguised from its use by the Indian "subaltern" historians who equate the postcolonial nation with the native bourgeoisie. Grmasci's idea of the hegominc nation with a socialist program rejects postcolonial populism. The subaltern group of peasants can speak through and with the struggle of the revolutionary nation emerging through the hegemonic united front guided by a proletarian party that has earned the support of the majority.
Keywords: Peasantry; Peasants